Entre o oratório e a profissão : formação de professoras na Escola Normal Rural Nossa Senhora Auxiliadora em Porto Velho/RO (1930-1946) - Prado, Fernanda Batista do (2017)
We analyzed the course of creation and implantation of the Escola Normal Rural NossaSenhoraAuxiliadora- ENRA, that originated in the years of 1930, like Escola Paroquial and from 1937 until 1946, began to offer the training course for rural normal teachers, with main objective of investigating how the institution educated the Porto Velho girls. From there, we analyzed the training courses offered by ENRA in Porto Velho focusing on the Normal Rural Course offered at the institution from 1937 to 1946. We tried to compose a historical record of the trajectory of this educational institution, understanding how the schooling of the students was given and the formation of primary teachers in the ENRA. We have as sources books ofata and registrations, books of promotions, terms of visits collected in the collection of the school institution, press and other documents found in the public archives of Mato Grosso and Porto Velho. Methodologically, we are based on Peter Burke (1992), Marc Bloch (2002), Michel De Certeau (1982), CarloGinzburg (1989) among other authors, who adopted the New History assumptions, to represent sources that could by themselves be considered true or that defined the past as a rigid event that couldn’t be changed. Corroborating the conception of these authors, Carlos Bacellar (2008) contributed to the understanding that the documents collected should be analyzed in detail, because the history shouldn’t be seen only from the whole, but also from the details, events and way of view of each historical subject. As for the study of Women's History and women's schooling, Guacira Lopes Louro (1997; 2010), Jane Soares de Almeida (1998; 2007) and Michelle Perrot (2007) were essential to understand the education and training imposed and apprehended by women. The studies of Ester Buffa and Paolo Nosella (1996; 2009) and Justino Pereira de Magalhães (2004) brought contributions to understand the history of educational institutions and helped us to define our categories of analysis. The categories of analysis defined were: the courses, the teachers and the rules of the school, in which we seek to analyze the conception of education adopted and practiced for the education of normal rural women in the Institution. An education we have learned for a long time has been denied to women. When they finally entered educational institutions, female education was marked by austere control in the name of a supposed religious and christian morality. The results showed evidence that the institution was conducted under the dogmas of the solid catholic confessional identity advocated by the norms imposed by Don Bosco, marked by the submission and acceptance of the Salesian beliefs. The Filhas de Maria Auxiliadora joined the leaders, who to provide formal and controlled education for their daughters, and the people of Porto Velho, who wanted to educate daughters and sons. The institution achieved its goals by educating a generation of women from the dogmas of catholicism that influenced other generations, in a distant place, neglected by its rulers. The school quickly became the InstitutoMaria Auxiliadora, still offering the first levels of education until the last years of high school to a wealthy PortoVelho social class.